The Urban Poles and their role in the decongestion on the big cities Case study of Ain Al-Nahas (Constantine) - Houari, Souad (Journal of Human Sciences, 2021)
The new urban politic adopted by Algeria in recent years, and its orientation toward the urban poles is a complement to the previous urban politics, already applied to control the urban growth of large cities. It is an important initiative for relieve pressure on them and minimize their roles at all levels administrative, services, industrial, educational and even of making decision, after the experiment failure of the new cities. In order to support this idea, we have examined the urban pole model Ain Nahas in the town of El Khroub (Constantine), which benefited from it Constantine to determine its response of the needs confrontation, Through the application of various urban projects of housing in various versions, Public facilities at their local and regional levels, and the several infrastructure, which can creates a completed urban unit within a structured and planned urban organization.